Parameters effective on survival in connective tissue disease-related interstitial lung disease - Atlı, Siahmet; Kirkil, Gamze; Kuluöztürk, Mutlu; Öner, Önsel; Koca, Suleyman Serdar; Aydın, Ayşe Murat; Doğru, Sibel (My University, 2024)
Aims: Connective tissue diseases (CTD) are systemic diseases that most commonly cause lung involvement. To examine how the disease will progress and survival at the time of diagnosis in connective tissue disease related interstitial lung disease (CTD-related ILD). Methods: Patients with radiological diagnosis of CTD-related ILD were included in this retrospective study. Seventy-five patients aged over 18 years, who were diagnosed as having ILD radiologically and rheumatoid arthritis, Sjögren’s syndrome, polymyositis/dermatomyositis, systemic sclerosis, ankylosing spondylitis, systemic lupus erythematosus. Patients who underwent high-resolution computed tomography, pulmonary function test, carbon monoxide diffusion capacity test, and 6-minute walk test were included in the study. During the 1-year follow-up period, the data of the patients who died and survived were compared. Results: Of the 75 patients included in the study, 55 were women and 20 were men. There were comorbidities in 56 (74.66%) patients. There was no statistical difference between the patients’ CTD subtype and FEV1, FVC, FEV1/FVC, DLCO, 6MWT distance, and 6MWT baseline oxygen saturation. At the end of the 1-year follow-up period, four patients died. Age, sex, smoking, CTD subtype, presence of comorbidities, and chronic obstructive pulmonary disease were not associated with survival, but it was determined that non CTD duration, the presence of CHF, DM, and a fibrosis rate of >10% were statistically significantly associated with survival. Among the serologic markers, ESR (60.25±17.72 vs. 24.52±18.96) and CRP (81.12±80.53 vs. 6.36±7.53) were found to be statistically significantly higher in patients who died; the levels of other markers were similar to patients who survived. FEV1, FVC, and 6MWT distances were significantly lower in patients who died. The presence of emphysema, air cysts, nodule, atelectasis, septal thickening, parenchymal bands, air trapping, honeycomb, opacity, ground-glass, mosaic attenuation, and bronchiectasis was not found to be associated with survival in HRCT. However, calcific nodules, pleural effusion, bronchial wall thickening, and fibrotic change were found to be statistically significantly associated with survival. Conclusion: We suggest that patients with CTD-related ILD with comorbidity, low baseline respiratory function parameters, a fibrosis rate of >10% on HRCT, calcific nodule, pleural effusion, bronchial wall thickening, and fibrotic changes should be followed more closely in terms of disease progression and mortality.
Keywords: Survey; interstitial lung diseases; Connective tissue diseases